Contribution to Knowledge of Contains on Peridotite Rocks of the Krivaja-Konjuh Ophiolitic Complex (Massif) - Operta, Mevlida (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2017)
Krivaja-Konjuh ultramafic complex is mainly constructed of ultramafic rocks associated with different varieties of igneous rocks (gabbro, dolerite, diabase, spilite, keratophyres, granitoids) and metamorphic rocks (amphibolites, amphibolite schists and eclogites). This paper presents results of mineralogical and chemical analysis of ultramafite rocks (peridotite-lherzolites) samples in the southern part of Krivaja-Konjuh massif. The samples were examined optically, by using method of X-ray fluorescence spectroscopy and electron microprobe method. Optical results showed that lherzolites have uniform textural characteristics and mineral composition. Results of chemical studies on these rocks demonstrated modal composition with high content of MgO, low content of CaO and high content of MgO:FeO (about 5 and up). Based on CIPW normative system, their composition is uniform with a very small variation in the content of diopside, with a slightly larger variation in the content of olivine. The rhombic pyroxene in composition correspond to enstatite and monoclinic pyroxenes are diopside by the composition. Spinel in peridotites are Al spinels and Al chromium spinels.